Bundles de Nanotubos de Carbono Intercalados com átomos de Rb e Cs: uma abordagem ab initio - ROCHA, Sara Ruth Ramos (2022)
In this work we study the insertion of zero, one, three and six rubidium and cesium atoms in the hexagonal lattice of (17,0) carbon nanotubes bundles using an ab initio calculations, based on Density Functional Theory (DFT), implemented in the SIESTA code. For the exchangecorrelation term, the LDA and GGA approximations were used. It was observed through the interleaving energy that the systems are stable and present, in modulus, higher interleaving energy in LDA approximation. The electronic properties of these systems are analyzed through band structures and projected density of states (PDOS). Results show that the quantity of Rb/Cs atoms inserted in the bundle modifies the band structures and the Fermi level is shifted to a region of higher density of states. As we increase the number of atoms intercalated in the bCNT, the Fermi level is shifted to the conduction band. Analysis of the electronic properties, both the Rb/bCNT and Cs/bCNT, indicates that the semiconducting characteristics of the (17,0) carbon nanotubes bundles aren’t preserved when they are intercalated with Rb/Cs, starting to present a metallic character.